The Evaluation of the Side Effects of Pegilated Interferon Monotherapy and Pegilated Interferon / Lamivudin Treatment in Patients With Chronic Hepatitis B - Demirdag, Kutbettin; karlidag, Gulden Eser (Galenos Yayincilik, 2009)
This study was planned to evaluate the clinical side effects occurred with pegylated interferon monotherapy, and pegylated interferon and lamivudine combined treatment in patients with chronic hepatitisB(CHB). A total of 54 patients diagnosed with CHB were divided into 4 treatment groups. Patients were evaluated at baseline and at 12th, 24th and 48th weeks of the treatment in order to determine systemic side effects (such as fever, flu-like syndrome, myalgia, fatigue, arthralgia, headache, anorexia, nausea, diarrhea, cough, concentration disorder, excessive sleep or insomnia, weight loss, loss of libido, hair loss, anxiety, delirium, suicidal ideation, and epilepsy). The most common systemic side effects were flu-like syndrome, myalgia, fatigue, concentration disorder, weight loss, and hair loss. There was no significant difference between the groups with respect to the occurrence of individual side effect during the treatment period. Whenthe groups were examined at 12th, 24th and 48th weeks of the treatment without considering the total treatment time there was significant difference between groups in terms of fever, anorexia, and excessive sleep (p< 0.05). The frequency of side effects had a tendency to decrease at 48th week of the treatment compared to 12th week. There was no statistically significant difference between groups in termsof treatment responses evaluated by appropriate criteria. In conclusion, there was no significant difference between two pegylated forms, as well as, between combined treatment and monotherapy with respect to systemic side effects and treatment outcomes.
Keywords: Chronic hepatitis B; pegylated interferon; side effects